PENETAPAN KADAR TANIN TOTAL EKSTRAK BIJI JINTAN HITAM (Nigella sativa) SECARA SPEKTROFOTOMETRI UV-VIS - Mukhriani Mukhriani; Faridha Yenny Nonci; Mumang Mumang (Universitas Islam Negeri Alauddin Makassar, 2014)
Researched about The Total Tannin Assay Extract of Black Cumin Seeds (Nigella sativa) with Ultraviolet-Visible Spectrophotometry. This research aims to determine the levels of total tannin extract of black cumin seeds (Nigella sativa). The method used is multilevel macerationusing n-hexane and ethanol 70%. Extracts were identified using FeCl3reagent and gelatin solution showed positive resultscontaining tannin onthe ethanol70%extract.The extracts thatpositive containing tannins diluted, added Folin Deanis reagent and saturated sodium carbonate, then read at 740 nm wavelength. Forming reaction was the oxidation reduction where tannin as reductant and Folin Denis as an oxidant. The results of oxidation will form a blue color that can be read at maximum wavelength. Based on the regression y = 0.004 x + 0.097 and 0.996 for determination coefficient, was gained an average of tannin levels in the ethanol extract of black cumin seeds (Nigella sativa) is 4, 13 %.